ANALYSIS THE TYPE OF DEIXIS IN THE MAIN CHARACTER ON THE MOVIE I LEAVE MY HEART IN LEBANON - Viahapsari, Evi; Parmawati, Aseptiana (IKIP Siliwangi, 2020)
This study aimed to describe the type of deixis on the main character in the film titled I Leave My Heart in Lebanon. This research is descriptive qualitative research.The data of this research was collected by analysis of the use of language spoken by the main character in the film I Leave My Heart in Lebanon, with the stages: 1) Organizing the data by collects of all the data in the movie that contains of deixis. 2) Categorizing the data into the types based on levinson theory who classified deixis into deixis persona, spatial, temporal, discourse, and social. 3) Analyzing the data which containing five types of deixis. 4) Present the sample of the data that related to the study, the researcher will present the result of the research some of each category. All of the sources taken on the Film I Leave My Heart in Lebanon. Based on data analysis, the researcher found 125 data that indicates the type of deixis. including personal, temporal, spatial, social, and discourse deixis. The deixis in this film are dominated by personal deixis with 102 data.